2018
DOI: 10.1038/gim.2017.238
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of family history to the burden of diagnosed diabetes, undiagnosed diabetes, and prediabetes in the United States: analysis of the National Health and Nutrition Examination Survey, 2009–2014

Abstract: These findings confirm that family history of diabetes has a major public health impact on diabetes in the United States. In spite of the recent interest and focus on genomics and precision medicine, family health history continues to be an integral component of public health campaigns to identify persons at high risk for developing type 2 diabetes and early detection of diabetes to prevent or delay complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
(34 reference statements)
1
18
0
1
Order By: Relevance
“…As missing data in the analysis dataset were around 10%, 10 imputations were performed to follow the recommendations. 27 All statistical analyses were performed with STATA/MP V. 16.…”
Section: Discussionmentioning
confidence: 99%
“…As missing data in the analysis dataset were around 10%, 10 imputations were performed to follow the recommendations. 27 All statistical analyses were performed with STATA/MP V. 16.…”
Section: Discussionmentioning
confidence: 99%
“…Our POP-ABC study findings, obtained from a large cohort of AA and EA with parental history of T2D, are remarkably concordant with the previous report from a smaller sample of a less diverse population [ 3 ]. Both studies found that weight maintenance or modest loss was associated with sustained normoglycemia, whereas modest weight gain (~1 kg/y) was associated with increased risk of incident prediabetes among individuals at perhaps the highest known risks for T2D, namely, Pima Indians [ 30 ] and people with parental diabetes [ 31 ]. Along with the prior report [ 3 ] and data from diabetes prevention trials [ 11 , 28 , 29 ], our present findings strengthen the notion that relatively modest changes in body weight could have disproportionate effects on glycemic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…73 FHH of diabetes is estimated to be the main cause of more than 15 million diabetic and pre-diabetic cases in the USA, but more than 1·4 million of these remain undiagnosed. 74 Similarly, Lynch syndrome affects an estimated 1 in 370 Americans, but less than 1·2% of these have been diagnosed. 75 In the current system, risk assessment is non-systematic and health care is provider-driven and dependent on the patient presenting to the health system, leading to low identification rates, non-guideline concordant care, and racial and socioeconomic disparities in identification and referral rates.…”
Section: Fhh and Population Healthmentioning
confidence: 99%